Respostas

2014-05-20T12:03:44-03:00
F(x)= x^(2-7x+10)
f(0)=0^(2-7.0+10)
f(0)=0^12
f(0)=0
2014-05-20T12:06:07-03:00
 f(x)= x elevado a 2 -7x+10 onde f:R .... R CALCULE F(0) 
f(x) = x² - 7x + 10
f(0)

então 
f(x) = x² - 7x + 10
f(0) = x² -7x + 10
 0  = x² = 7x + 10
x² - 7x + 10 = 0
a= 1
b= -7
c= 10
Δ= b² - 4ac
Δ= (-7)² - 4(1)(10)
Δ= 49 - 40
Δ= 9
se 
Δ > 0
então
x = - b - + 
√Δ2a

x¹ = -(-7) - 
√9/2(1)
x¹ = + 7 - 3/2
x¹ = 4/2
x¹ = 2

x"  = -(-7) + 
√9/2(1)
x" = + 7 + 3/2
x" = + 10/2
x" = 5
 
V = { 2,5}